Effect of intratympanic dexamethasone injection in sudden idiopathic sensorineural hearing loss - Swamy, K. Mallikarjuna; Ganiger, Arati (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: The aim of this study is to assess the effect of intratympanic dexamethasone injection (ITDI) in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). Methods: A prospective study was conducted on 40 patients refractory to intravenous steroid therapy between May 2012 to March 2014. Intratympanic dexamethasone injection was given every week for 3 consecutive weeks. Hearing was assessed by performing pure tone audiogram before every ITDI and also 1 week after the completion of treatment. Results: Hearing improvement was seen in 27 out of the 40 cases (68%). Conclusions: Intratympanic dexamethasone significantly improves the prognosis of ISSNHL and is a safe, inexpensive and effective treatment in ISSNHL.